A leitura no contexto de privação de liberdade : análise da abordagem de leitura no livro didático - Pereira, Marlei Cleis (2015)
Working with reading in the classroom is a hot topic and researched at present, due to its great importance for the development of students in all school subjects. In this perspective, this work is devoted to an investigation into how reading has been crafted from the textbook, being that often the only tool that teachers have available to their students. We focus, however, in the education of students of private freedom, which are admitted in the Centro de Socio Educação de Campo Mourão, and how they receive schooling along the lines of the Educação de Jovens e Adultos, they use the same teaching materials. We analyzed, then, the book Educação de Jovens e Adultos written by Cicero de Oliveira Silva, Elizabeth Gavioli de Oliveira Silva and Greta Nascimento Marchett, published in 2013 by IBEP, which was the textbook chosen by teachers for use by students in the year 2015 in the CEEBJA of Campo Mourão. We seek to find out What`s the Our goals are to analyze the reading of this approach in the textbook in question and propose reading activities to adapt this material for socioeducation, seeking a more pleasant work for students and a more effective result. As a theoretical basis for the development of the analysis and proposal, we resort to recognized authors like Sole (1998), Leffa (1996, 1999) and Kleiman (2013). During the analysis, we realized that the authors of the textbook did a diverse work with reading activities, however, there is not a proper introduction to the reading of most texts. Activities are proposed, mostly to occur only after the reading, and the issues prioritize superficial understanding of the text, and the opinion of the student, regardless of text content, with few questions of interpretation. What predominates, then, it is the approach to the text perspective or the student, if neglecting the caller and interactive perspective. In order to adapt, we propose to exchange some texts by others who deem most appropriate, the introduction of texts through activities before reading, attempting to better understanding through activities during the reading and the addition of some issues understanding and interpretation to the activities proposed by the authors.